Identification of CWH43 as a novel prognostic biomarker and therapeutic target in clear cell renal cell carcinoma by a multi-omics approach and correlation with autophagy progression - Ailian Wu; Peng Bai; Hui Qu; Tao Zhang (Discover Oncology)
Abstract Background Clear cell renal cell carcinoma (ccRCC) poses significant challenges due to its asymptomatic nature and poor prognosis at advanced stages. Identifying novel biomarkers is essential for enhancing prognostic accuracy and therapeutic strategies. This study explores the CWH43 gene, utilizing multi-omics data to determine its role in ccRCC. Methods Genomic, transcriptomic, and methylation data from TCGA-KIRC and GEO databases were analyzed to evaluate CWH43 expression and clinical impact. Bioinformatics tools assessed correlations with patient outcomes and pathway involvement. Results CWH43 expression was significantly reduced in ccRCC tissues and correlated with advanced disease stages and poor patient survival. Enrichment analyses revealed CWH43's involvement in critical cancer pathways, such as autophagy and immune response modulation, suggesting its significant role in ccRCC pathophysiology. Lower CWH43 levels were associated with increased tumor progression and immune evasion, impacting the tumor microenvironment. Conclusion This study highlights the utility of multi-omics data in identifying CWH43 as a novel prognostic biomarker for ccRCC. Integrating CWH43 into clinical practice could refine prognostic assessments and guide personalized therapy strategies, aligning with advancements in modern oncology. Further research is warranted to explore CWH43's mechanisms and therapeutic potential.